Adverse Pregnancy Outcomes Using The International Association of the Diabetes and Pregnancy Study Groups Criteria: Glycemic Thresholds and Associated Risks. Issue 1 (July 2015) - Sacks, David A.; Black, Mary Helen; Li, Xia; Montoro, Martin N.; Lawrence, Jean M.
Abstract : OBJECTIVE: To compare the risks of selected adverse pregnancy outcomes among untreated women who met The International Association of the Diabetes and Pregnancy Study Groups (IADPSG)–defined glucose criteria at two different thresholds. METHODS: A retrospective cohort study of women tested for gestational diabetes mellitus (GDM) with the 75-g 2-hour glucose tolerance test (GTT) who delivered a live singleton neonate. Data of women who were treated because they met institutional criteria defining GDM (at least two GTT results greater than or equal to fasting 100 mg/dL, 1-hour 195 mg/dL, and 2-hour 160 mg/dL) were excluded. The data of the remaining women were analyzed in three groups. The prevalence of selected adverse pregnancy outcomes was compared for those with no GDM ("no GDM, " n=7, 943); those at least one of whose results were fasting 92–94 mg/dL, 1-hour 180–190 mg/dL, or 2-hour 153–161 mg/dL ("GDM-1, " n=771); and those at least one of whose results were greater than or equal to fasting 95 mg/dL, 1-hour 191 mg/dL, or 2-hour 162 mg/dL ("GDM-2, " n=1, 121). RESULTS: Of the 9, 835 women, 1, 892 (19.2%) met criteria for GDM, of whom 771 (40.8%) were categorized as GDM-1 and 1, 121 (59.2%) GDM-2. After adjustment for confounders, women with GDM-2 were at significantly greater risk for preeclampsia or eclampsia, preterm delivery, primary cesarean delivery, shoulder dystocia, higher birth weight, ponderal index, large for gestational age, transient tachypnea, and neonatal hypoglycemia than women without GDM. Only birth weight and large for gestational age were significantly greater in the GDM-1 compared with the no GDM group. CONCLUSION: Fewer adverse outcomes are found at lower levels of the IADPSG-defined glucose intolerance spectrum. Determining whether these patients will benefit from treatment will require a randomized controlled trial. LEVEL OF EVIDENCE: II Abstract : Women with lower levels of The International Association of the Diabetes and Pregnancy Study Groups–defined gestational diabetes have fewer adverse outcomes than those with higher glucose tolerance test results.